1997
DOI: 10.1128/aem.63.2.380-386.1997
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of two bifunctional chitinases/lysozymes extracellularly produced by Pseudomonas aeruginosa K-187 in a shrimp and crab shell powder medium

Abstract: Two extracellular chitinases (FI and FII) were purified from the culture supernatant of Pseudomonas aeruginosa K-187. The molecular weights of FI and FII were 30,000 and 32,000, respectively, by sodium dodecyl sulfate-polyacrylamide gel electrophoresis and 60,000 and 30,000, respectively, by gel filtration. The pIs for FI and FII were 5.2 and 4.8, respectively. The optimum pH, optimum temperature, pH stability, and thermal stability of FI were pH 8, 50؇C, pH 6 to 9, and 50؇C; those of FII were pH 7, 40؇C, pH 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
59
0
10

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(75 citation statements)
references
References 45 publications
(56 reference statements)
5
59
0
10
Order By: Relevance
“…V2 was 60°C (Nawani et al 2002) and from Aeromonas sp. DYU-too7 (Lien et al 2007), Pseudomonas aeruginosa K-187 (Wang and Chang 1997), Cellulomonas flavigena NTOU 1 (Chen et al 1997) and Bacillus sp.BG-11 was 50°C (Bhushan and Hoondal 1998). ChiIO8 was also observed to be stable up to 60°C for 60 min, whereas other heat-stable chitinase activities such as a novel thermostable chitinase from Thermomyces lanuginosus SY2 (Guo et al 2008) and a thermostable chitinase from Planococcus rifitoensis strain M2-26 (Essghaier et al 2009) were found to be decreased at high temperature for a long time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…V2 was 60°C (Nawani et al 2002) and from Aeromonas sp. DYU-too7 (Lien et al 2007), Pseudomonas aeruginosa K-187 (Wang and Chang 1997), Cellulomonas flavigena NTOU 1 (Chen et al 1997) and Bacillus sp.BG-11 was 50°C (Bhushan and Hoondal 1998). ChiIO8 was also observed to be stable up to 60°C for 60 min, whereas other heat-stable chitinase activities such as a novel thermostable chitinase from Thermomyces lanuginosus SY2 (Guo et al 2008) and a thermostable chitinase from Planococcus rifitoensis strain M2-26 (Essghaier et al 2009) were found to be decreased at high temperature for a long time.…”
Section: Discussionmentioning
confidence: 99%
“…G-1 (Park et al 1997) and Ps. aeruginosa K-187 (Wang and Chang 1997), whereas the chitinase from T. lanuginosus SY2 (Guo et al 2008) had the highest activity at pH 4Á5, Aeromonas sp. DYU-too7 (Lien et al 2007) and Bacterium Ralstonia sp.…”
Section: Discussionmentioning
confidence: 99%
“…A 40 kDa chitinase from Pseudomonas sp. TKU008 [31] and 50 kDa chitinase from P. aeruginosa K-187 [32] has been reported to have an optimum temperature of 50°C, whereas the optimum pH of 5.0 is similar to many bacterial chitinases including Aeromonas sp. DYU-Too7 [33], Bacillus circulans WL-12 [34], and Streptomyces sp.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibited activity of this enzyme in the presence of PMSF, an inhibitor of cysteine and serine enzymes, additionally confirms this conclusion. Other results were presented for bifunctional chitinases/lysozymes by Pseudomonas aeruginosa K-187 [42]. A metal ion-chelating compound (EDTA) had no inhibitory effect on the enzyme activity, which suggests a lack of relation between the catalysis mechanism of this enzyme A similar phenomenon occurred for chitinases A from B. thuringiensis and from Serratia sp.…”
Section: Discussionmentioning
confidence: 68%